Recent observations on the distribution of the endangered butterfly Eresia erysice erysice (Geyer, 1832) (Lepidoptera: Nymphalidae) - Vila-Verde, Gabriel; Delabie, Jacques Hubert Charles (EntomoBrasilis, 2024)
The Brazilian endemic butterfly Eresia erysice erysice (Geyer, 1832) (Lepidoptera: Nymphalidae) has been included in the Official List of Brazilian Endangered Fauna as critically endangered (CR). Until now, this rare butterfly has only been known to inhabit Atlantic Forest fragments in the “Hileia Baiana”. This paper presents updated information on occurrences of E. e. erysice. A male and a female specimens were collected in a disturbed forest fragment near the experimental fields of the Centro de Pesquisas do Cacau (CEPEC), Ilhéus, Bahia. These new findings indicate that the distribution boundary of this subspecies extends about 80 km more to the north and suggest that it is not as exclusive to forest habitats as previously thought.